Inkonsistensi Putusan Mahkamah Konstitusi dalam Memutus Perpanjangan Masa Jabatan Ketua Komisi Pemberantasan Korupsi - Siletty, Yondri; Irham, Muhammad; Soplanit, Miracle (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2025)
The Constitutional Court or hereinafter abbreviated as MK is one of the judicial institutions that has a very important role in guarding and maintaining the constitution. To carry out this role, MK has the authority to conduct judicial review in the form of testing a law to ensure that the law formed by the legislator does not conflict with higher norms, namely the Constitution. However, in exercising this authority, MK in several of its decisions often causes polemics in the community due to the inconsistency of decisions experienced by the court in deciding similar cases. As in the case of testing the institutional term of office, which has been tested several times to MK but has different verdicts, where the majority of the MK decisions consistently reject and do not grant the applicant's request in this type of case, but on the other hand there are MK decisions that grant the applicant's request to extend the existing term of office, such as MK Decision Number 112/PUU-XX/2022 which extends the term of office of the leadership of the KPK from 4 to 5 years. This writing uses a Normative Juridical research type, with a statutory approach, conceptual approach. This research shows that the MK has experienced inconsistency in its stance when compared to several similar MK decisions that have examined the issue of the term of office of other independent institutions and that the Decision a quo has given rise to the meaning of existing legal consequences.